General characteristics of hydrocarbon oxidazing microorganisms allocated from oil- polluted soils of Azerbaijan - Babayeva, Irada; Qasimova, Svetlana (ScienceRise: Biological Science, 2017)
Aim of research – the study of microorganisms of different oil-polluted soils (OPS) of Azerbaijan. Methods of research. The objects of the research were samples of soils from two studied deposits: Naftalan and apsheron ones – Bibi-Eibat and Binagadi. The quantitative account of microorganisms was carried out by the method of limit dilutions. The conversion degree was determined by the weight method. Results of research. The results of the realized researches demonstrated that among 108 isolated fungal strains, 69 were isolated from oil-polluted Apsheron soils, 21 strains – from Naftalan oil deposits, 14 strains - from Naftalan oil, 4 strains – from used Naftalan oil. It was revealed that Penicillium sp.3п strain, isolated from Naftalan oil deposit soils, is most active. Conclusions. The isolation of more quantity of hydrocarbon oxidizing microorganisms (especially fungi) from soils of Binagadin oil deposits is explained by the presence of the large number of n-alkanes in its content. The results of conversion of Naftalan oil and its fractions by isolated active strains give a ground to suppose that the prevailing activity of Penicillium sp.3п strain is connected with its substrate specific properties